(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The paper starts from the definition of competency and then discusses the competencies that librarians employed in academic libraries must have so that the library could provide their mission. The requirements of the scientific community as a dynamic category go towards the achievement of the knowledge society, and therefore they change and improve methods of evaluating its productivity. Measurement and evaluation of the overall scientific creativity is an extremely demanding job that must be made by competent professionals. The paper informs on qualitative and quantitative: bibliometrics, sociometrics, altmetrics and other methods that can be used for evaluation of scientific production. It presents and explains the new competency profile which the scientific community requires from the academic library as a service user and special attention is paid to the possible role and place of the library in the evaluation of scientific productivity. This paper is designed to provide information on the new competencies that the library must have if it is involved in the provision of various metric services. In this regard, possibilities of the academic library as a partner in measuring and increasing scientific productivity are discussed. It is explained how academic libraries can adapt to their new role. Furthermore, it is attempted to answer the question in which direction education of librarians should move in order to realize this partnership. Keywords: Bibliometrics, librarian competencies, academic libraries, evaluation of scientific productivity